Comparison of urinary and plasma ketone using urinary nitroprusside strip in patients with diabetic ketoacidosis - Noori, Farid; Mohammadi-Kebar, Sousan; Mohammadi-Kebar, Yousef; Ghavami, Maryam; Isazadehfar, Khatereh (International Journal of Research in Medical Sciences, 2023)
Background: Diabetic ketoacidosis is one of the most important and serious acute complications of diabetes and one of the medical emergencies that has been the most common cause of death in patients with diabetes. Prompt diagnosis and therapeutic intervention play an important role in reducing complications and mortality. The aim of this study was to compare urinary and plasma ketones using urinary nitroprusside strip in patients with diabetic ketoacidosis. Methods: In this cross-sectional study, 38 diabetic ketoacidosis patients were included in this study during the years 2017 and 2018 in the emergency department of Imam Khomeini hospital in Ardabil city. To test for plasma ketones, 2 cc of venous blood samples were taken and transferred to the laboratory for plasma isolation. The resulting plasma was examined with a urine dipstick and the discoloration was recorded. This was repeated at 0, 6 and 12 o’clock for serum ketones. All patients received their treatment according to the treatment protocol of diabetic ketoacidosis and urine ketone, PH and bicarbonate and BE patients were measured routinely. Results: Serum ketones were positive in all patients and 34 patients had positive urinary ketones. In this study, serum ketone levels were significantly correlated with blood acidity at baseline and with bicarbonate and basal arterial gas deficit at all three stages. However, urinary ketones had a significant correlation with blood acidity at baseline and at 12 hours, with bicarbonate at baseline and with arterial gas deficiency at 12 hours. Conclusions: The results showed that examination of plasma ketones with dipstick can be a useful, rapid and accurate clinical trial for the diagnosis of diabetic ketoacidosis in patients with diabetes.